IMPROVING STUDENTS’ CHEMICAL LITERACY SKILLS THROUGH PROBLEM-BASED LEARNING MODELS ON STOICHIOMETRY TOPICS - Ade Trisnawati; Adinda Amelia Permatasari; Meilisa Rusdiana Surya Efendi (Universitas Negeri Surabaya, 2026)
The purpose of this study was to determine students’ chemical literacy skills after being taught stoichiometry using a problem-based learning model. The Research design is a pre-experimental design with a one-group pretest-posttest design. The sample in this study was 13 new students of Chemical Engineering at PGRI Madiun University in the 2025/2026 academic year. Data collection used a context-based chemical literacy test carried out before and after PBL learning. Based on the Research, the pretest results showed that 100% of students had low chemical literacy, while the posttest results showed that 74% had low chemical literacy and 16% had moderate chemical literacy. Then, the analysis of students' chemical literacy levels from their pretest answers showed the highest percentage at the Scientific Illiteracy Level (72%) and the posttest results showed the most significant percentage at the Functional Scientific Literacy Level (32%). The implementation of PBL to improve students’ chemical literacy skills should consider several factors, such as the lecturer’s support for learning, the selection of material topics, information on students’ misconceptions in stoichiometry, and alignment between the activity design and targeted literacy indicators.